2018
DOI: 10.1002/lno.11098
|View full text |Cite
|
Sign up to set email alerts
|

Coregulation of nitrous oxide emissions by nitrogen and temperature in China's third largest freshwater lake (Lake Taihu)

Abstract: Nitrous oxide (N 2 O) is a potent greenhouse gas and contributes to the loss of stratospheric ozone. However, the role of inland waterbodies in the dynamics of atmospheric N 2 O is poorly understood. We investigated N 2 O fluxes and their controlling factors in Lake Taihu, a large and shallow (2400 km 2 , 1.9 m depth) eutrophic lake in eastern China. Long-term measurements (2011-2016) revealed spatial and temporal variations in the lake surface N 2 O fluxes. The mean N 2 O flux from the lake was 3.5 AE 1.8 (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 75 publications
(175 reference statements)
4
16
0
Order By: Relevance
“…Agricultural and urban rivers are hotspots where the N 2 O emissions from freshwater systems are significantly impacted by anthropogenic activity . In this study, N 2 O fluxes were higher in agricultural rivers than urban rivers, which was consistent with previous studies on Lake Taihu which showed higher N 2 O fluxes in the northwestern area than the northern area. , Both dissolved N 2 O concentrations and N 2 O fluxes in the agricultural rivers of the Taihu watershed were higher than the estimated global mean values for rivers and streams (51.9 nmol L –1 and 41.1 μmol m –2 d –1 ) . However, the dissolved N 2 O concentrations and N 2 O fluxes in the urban rivers of the Taihu watershed were lower than the global mean values and were at the lower range of measurements from other urban rivers (Table S7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Agricultural and urban rivers are hotspots where the N 2 O emissions from freshwater systems are significantly impacted by anthropogenic activity . In this study, N 2 O fluxes were higher in agricultural rivers than urban rivers, which was consistent with previous studies on Lake Taihu which showed higher N 2 O fluxes in the northwestern area than the northern area. , Both dissolved N 2 O concentrations and N 2 O fluxes in the agricultural rivers of the Taihu watershed were higher than the estimated global mean values for rivers and streams (51.9 nmol L –1 and 41.1 μmol m –2 d –1 ) . However, the dissolved N 2 O concentrations and N 2 O fluxes in the urban rivers of the Taihu watershed were lower than the global mean values and were at the lower range of measurements from other urban rivers (Table S7).…”
Section: Discussionsupporting
confidence: 91%
“…Lake Taihu is the third largest (2400 km 2 ) freshwater lake in China. Riverine inflow mainly comes from rivers to the northwest and north and outflows via rivers to the east . Land use information of the Taihu watershed was acquired from the Globeland30 website () using ArcGIS (version 10.7) (Figure B).…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catchment has nearly 200 rivers and canals connected to the lake without winter ice cover. The anthropogenic pollutant discharge into the lake through inflow rivers has been shown to be high but strongly variable among years; for example, the total nitrogen (TN) input decreased from 7.55 × 10 4 t in 1994 to 3.87 × 10 4 t in 2015 (Qin et al 2007; Xiao et al 2019). The local region features a subtropical climate with a low water temperature (monthly mean: 3.9°C) and precipitation (monthly mean: 60 mm) in winter and a peak (water temperature: 31°C; precipitation: 170 mm) in summer (Xiao et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Water samples were collected at 20‐cm depth using a custom‐made sampler equipped with a rubber cork, flushed into the 55‐ml preweighted serum glass bottles for two to three times, and then completely filled to the top of the bottles. About 0.2 ml of saturated HgCl 2 solution was added to the bottles for inhibiting bacterial activity (Borges et al, 2018), and the glass bottles were then immediately sealed with an open‐topped screw cap equipped with a halobutyl rubber septum to exclude any air bubbles (Borges et al, 2018; X. F. Wang, He, et al, 2017; Xiao et al, 2019). The water samples were subsequently stored in an ice‐packed cooler, transported back to the laboratory, and analyzed within 48 hr.…”
Section: Methodsmentioning
confidence: 99%